Quality control of proteins mislocalized to the cytosol - Hegde, Ramanujan (Henry Stewart Talks, 2017)
Protein maturation is monitored for failures, Failures of protein localization in vitro and in vivo, Mislocalized proteins are selectively recognized, Relationship between protein maturation & quality control, Mitochondrial proteins are also prone to mislocalization, Recognition of mislocalized mitochondrial proteins, Protein aggregates can disrupt protein quality control, Key concepts and the future of protein quality control